The startling story of the stolen statue - Abbott, Tony, 1952- (Abbott, Tony, 1952- Goofballs, 2012)
As Badger Point School is preparing to celebrate its 100th anniversary, the statue of its founder, Simon Plunkett, goes missing but the Goofballs are quickly on the case, looking for evidence and following clues.